Pengaruh Kesehatan Keselamatan Kerja (K3), Kompetensi dan Lingkungan Kerja terhadap Kinerja Tenaga Kerja Melalui Kepuasan Kerja sebagai Variabel Mediasi (Kajian Studi Literatur Manajemen Sumber Daya Manusia) - R. Kanaf, Yohanes; E.H.J. FoEh, John; A. Manafe, Henny (Dinasti Review Publisher, 2023)
In this scientific work, the aim is to explore and formulate hypotheses regarding the impact of occupational health and safety (K3), competency, and work environment on workforce performance, with job satisfaction being the intermediary or mediating variable. The focus of this scientific work lies in the aspect of human resource management, recognizing the importance of K3, competency, and work environment in improving workforce performance, which in turn will contribute to company productivity. To achieve this goal, a library study approach is applied to collect and analyze information from various references that are relevant to the subject matter being discussed. This literature review involves analysis of articles, scientific journals, and related research that has been conducted previously. The purpose of this literature review is to understand the relationship between variables in previous research, as well as provide a basis for future thesis research to be carried out.